Specific Skin Infiltration as First Sign of Localized Stage Hodgkin's Lymphoma Involving an Epitrochlear Node. (June 2015) - Llamas-Velasco, Mar; Fraga, Javier; Pérez-Gala, Silvia; Cannata, Jimena; Kempf, Werner; Adrados, Magdalena; García-Diez, Amaro
Abstract : Abstract: Cutaneous manifestation as the first sign of Hodgkin lymphoma (HL) is very rare and diagnostically challenging; especially, because the clinical presentation of specific skin involvement by HL is polymorphous. We present a 44-year-old man with erythematous indurate papules and plaques in the right forearm and arm where skin biopsy showed an HL. He also has an enlarged epitrochlear node, and later histopathologic study confirmed the diagnosis of HL subtype–mixed cellularity. Immunohistochemical stains in both biopsies showed that the atypical cells were positive for CD30 and CD15, and negative for CD20 and CD3. PAX5 stained the nuclei of the atypical large lymphoid cells weakly and Oct-2 staining was negative in the atypical cells. EBER and LMP1 protein were negative in both biopsies. Epitrochlear involvement in HL, like in our case, is a rare event (<1%). We reviewed data about prognosis, clinical appearance, and treatment of all the cases of HL specific skin involvement published after Sioutos et al, emphasizing the cases where HL specific skin involvement was the first sign of the disease as in our patient.